Temporal Dynamics of Soil Virus and Bacterial Populations in Agricultural and Early Plant Successional Soils - Roy, Krishnakali; Ghosh, Dhritiman; DeBruyn, Jennifer M.; Dasgupta, Tirthankar; Wommack, K. Eric; Liang, Xiaolong; Wagner, Regan E.; Radosevich, Mark (Frontiers in Microbiology, 2020)
As reported in many aquatic environments, recent studies in terrestrial ecosystems implicate a role for viruses in shaping the structure, function, and evolution of prokaryotic soil communities. However, given the heterogeneity of soil and the physical constraints (i.e., pore-scale hydrology and solid-phase adsorption of phage and host cells) on the mobility of viruses and bacteria, phage-host interactions likely differ from those in aquatic systems. In this study, temporal changes in the population dynamics of viruses and bacteria in soils under different land management practices were examined. The results showed that bacterial abundance was significantly and positively correlated to both virus and inducible prophage abundance. Bacterial and viral abundance were also correlated with soil organic carbon and nitrogen content as well as with C:N ratio. The seasonal variability in viral abundance increased with soil organic carbon content. The prokaryotic community structure was influenced more by land use than by seasonal variation though considerable variation was evident in the early plant successional and grassland sites. The free extracellular viral communities were also separated by land use, and the forest soil viral assemblage exhibiting the most seasonal variability was more distinct from the other sites. Viral assemblages from the agricultural soils exhibited the least seasonal variability. Similar patterns were observed for inducible prophage viral assemblages. Seasonal variability of viral assemblages was greater in mitomycin-C (mitC) induced prophages than in extracellular viruses irrespective of land use and management. Taken together, the data suggest that soil viral production and decay are likely balanced but there was clear evidence that the structure of viral assemblages is influenced by land use and by season.